The Role of Glutathione-S Transferase in Psoriasis and Associated Comorbidities and the Effect of Dimethyl Fumarate in This Pathway - Campione, Elena; Mazzilli, Sara; Di Prete, Monia; Dattola, Annunziata; Cosio, Terenzio; Lettieri Barbato, Daniele; Costanza, Gaetana; Lanna, Caterina; Manfreda, Valeria; Gaeta Schumak, Ruslana; Prignano, Francesca; Coniglione, Filadelfo; et al. (Frontiers in Medicine, 2022)
Psoriasis vulgaris is a chronic inflammatory skin disease characterized by well-demarcated scaly plaques. Oxidative stress plays a crucial role in the psoriasis pathogenesis and is associated with the disease severity. Dimethyl fumarate modulates pro-inflammatory transcription factors activity. This is responsible for the downregulation of inflammatory cytokines and an overall shift from a pro- inflammatory to an anti-inflammatory/regulatory response. Both steps are necessary for the amelioration of psoriatic inflammation, although additional mechanisms have been proposed. Several studies reported long term effectiveness and safety of dimethyl fumarate monotherapy in patient with moderate-to-severe psoriasis. Furthermore, psoriasis is a chronic disease associated often to metabolic comorbidities, as obesity, diabetes, and cardiovascular diseases, in which glutathione-S transferase deregulation is present. Glutathione-S transferase is involved in the antioxidant system. An increase of its activity in psoriatic epidermis in comparison with uninvolved and normal epidermal biopsies has been reported. Dimethyl fumarate depletes glutathione-S transferase by formation of covalently linked conjugates. This review investigates the anti-inflammatory role of dimethyl fumarate in oxidative stress and its effect by reducing oxidative stress. The glutathione-S transferase regulation is helpful in treating psoriasis, with anti-inflammatory effect on the keratinocytes hyperproliferation, and in modulation of metabolic comorbidities.